The Translation of English Passive Voice into Indonesian - Herlina Lindaria Simanjuntak (TEKNOSASTIK, 2019)
English and Indonesian have different grammatical patterns and cultural values. That is why, many problems that students studying translation subject have to face. One of them is how to translate English Passive Voice into Indonesian. That is the reason the writer aims to do the research. The research is to describe the translation of English passive voice into Indonesian by analyzing two novels, which are Kristan Higgins’ Waiting on You and its translation Nina Andiana’s Penantian Terpanjang. This research uses qualitative method. The writer collected, identified, the data concerning with the translation of English passive voice. The results of the research shows that there are two categories of translating English passive voice into Indonesian, namely English passive voice can be translated both into Indonesian passive voice and English passive voice can be translated into Indonesian active voice. English passive voice is translated into Indonesian passive voice by using prefixes di- and ter-, meanwhile English passive voice is translated into Indonesian active voice by using prefixes me-, men-, and ber-. From forty one data which are identified there are 32 data (78.04%) of English passive voices translated into Indonesian passive voices and 9 data (21.96%) of English passive voices translated into Indonesian active voices.